(untitled) (Bangladesh Journal of Neuroscience, 2019)
Background: Stroke is the third leading cause of death in adult population throughout the world and is the most common cause of severe adult physical disability. The aim of the study is to identify the major risk factors in various subtypes of ischemic stroke according to TOAST criteria. Methods: A Cross-sectional observational study was conducted from January, 2018 to December 2018 in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. All the patients of first ever ischemic stroke within 14 days diagnosed by history, clinical examination and neuroimaging (CT scan of head / MRI of brain), meeting the inclusion and exclusion criteria were included in the study. Results: Present study showed that among the 52 ischemic stroke patients mean age of the respondents was 57 ± 12.37 years with a slightly higher male predominance. Male to female ratio was 1.2:1. Dyslipidemia 44 (84.6 %) and hypertension 37 (71.2 %) were the most common risk factors, followed by obesity and overweight 33(63.5%), smoking 32 (61.5%), diabetes mellitus 29 (55.8%), family history of vascular event 27(51.9 %) and past history of vascular event 14 (26.9%). TOAST Subtype distribution of study population was large-artery atherosclerosis 18 (34.6%) followed by cardioembolism 11(21.2%), small-vessel occlusion 10(19.2%), stroke of other determined etiology 3(5.8%), and stroke of undetermined etiology 10(19.2 %) of patients. In cardioembolic subtype significant association was found with ischemic heart disease (P=0.001) and chronic rheumatic heart disease (P= <0.001). Conclusion: In this study large-artery atherosclerosis was the most common subtype, followed by cardioembolism, small vessel occlusion, stroke of undetermined etiology and stroke of other determined etiology subtypes. Dyslipidemia was found to be the most common risk factor, others were HTN, diabetes and smoking. Ischemic heart disease and rheumatic heart disease were very important cause and comorbidities of cardioembolic types of ischemic stroke. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 14-21